Perancangan Penyalaan Engine Sepeda Motor Berbasis Arduino Melalui Bluetooth Android - Muhammad Ridha Fauzi (Jurnal Surya Teknika, 2021)
Motorcycle ignition which also functions as a motorcycle safety needs to be designed and made as safe as possible to avoid the loss of the vehicle from theft cases. This equipment is designed to turn on/off and search for motorcycles using a remote from a smartphone with an android operating system via a bluetooth network. The bluetooth input is controlled using the Arduino Uno microcontroller. From the test results, it is found that the maximum distance that can be achieved between Android and Bluetooth to operate a motorcycle engine is about 10 meters. This system also makes our motorcycle engine ignition a smart ignition.